Construction of gender development indicators for Jamaica : sector studies - Mohammed, Patricia (PIOJ/UNDP/CIDA KingstonJM, 2000)
Elucidates the background of gender relations in the Jamaican society from which the Gender-related Development Index and Gender Empowerment Measure were determined. Renders in each paper a contemporary reading and interpretation of gender dynamics in a selected sphere of economy and society in Jamaica.